(untitled) (Journal of Hama University, 2021)
Pregnancy at a young age is one of the most common phenomena in many societies and one of the most important health and social problems for the mother, family, society, health workers and governments around the world, and It is associated with the occurrence of many serious complications associated with pregnancy and childbirth, which are higher in young mothers compared to Adult mothers, Therefore, the present retrospective descriptive study was conducted to assess the effect of pregnancy and childbirth on the health status of a sample of 200 women in the Eighth Health Center, and they were chosen by the convenience sample method, and the data were collected using a questionnaire developed by the researcher. The results showed that young mothers have a higher rate of: delays in seeking health care during pregnancy, and in the occurrence of anemia, breast engorgement and cracked nipple and in the continuation of complications after childbirth compared with adult mothers. And the study recommended conducting educational courses to educate women about the risks associated with pregnancy at a young age on the health status of the mother, in addition to conducting a similar, broader and more comprehensive study at the country level on the effect of pregnancy and childbirth among young mothers versus Adult mothers on the health status of the mother.